The Effects of Zingiber officinal R. on Primary Dysmenorrhea - P Rahnama; H Fallah Huseini; H Mohammadi; M Modares; K Khajavi Shojaee; M Askari; P Mozayani (Institue of Medicinal Plants, ACECR, 2010)
Background: Prevalence of dysmenorrhea and its importance for women life as well as side effects of non steroid anti inflammatory drug used for its treatment increases the tendency for alternative complementary, and herbal therapy. Objective: This study was carried out to determine the effect of Zingiber officinale R. on primary dysmenorrheal on students residing in Dormitorieschr('39') Shahed University. Methods: This clinical trial was performed on 78 unmarried students, average 21 years old with primary dysmenorrhea residing in Dormitorieschr('39') Shahed University. Subjects were selected through a questionnaire which included demographic and menstrual cycle characteristics and graded of dysmenorrhea. Graded of dysmenorrhea were determined by verbal multidimensional scoring system and subjects who were graded moderate and severe dysmenorrhea were randomly allocated into two groups that received the Zingiber capsule and the placebo capsule. The subjects in Zingiber group received the 500 mg zingiber powders in capsules three times a day for three days and placebo group received 500 mg placebo capsule similarly from a day of starting of menstruation. Severity and duration of dysmenorrheal pain were determined in both groups and compared to each other. Results: Results indicate that demographic characteristics (age, BMI and menstrual status) were similar between two groups before treatments. Severity and duration of dysmenorrhea in Zingiber group deceased significantly (p<0.01 and p<0.021 respectively) at the end of the study compared to placebo group. Conclusion: Administration of zingiber 500 mg t.i.d decreases pain and duration of primary dysmenorrhea without any obvious adverse effects. The investigation for accurate effective doses of Zingiber and its adverse effect on long term administration is recommended.